ANALYSING NATIONAL INVESTMENT FROM A MAQASID SHARIAH PERSPECTIVE: UNDERSTANDING ECONOMIC IMPACT AND PUBLIC INTEREST - Kamaluddin, Imam; Rahma, Fenita Wildani; Indallah, Sayyid Muhmmad (IBN KHALDUN BOGOR, 2023)
The discourse on investment is important to discuss. This relates to the Islamic investment model in Indonesia being below conventional investment, both in terms of quality and amount of capital and market share. Therefore, if conventional investments are regarded as haram according to Islamic law, this could have a negative impact on the image of the conventional investment market in the future. The purpose of this study is to re-clarify the understanding of investment law in Islam, particularly in the context of conventional investments. In the preparation of the paper, the author uses a descriptive-analytical approach to re-evaluate the law of investment in Islam. The results of this study conclude that although investments that promise huge profits with minimal effort are considered a reasonable practice and can be done because they have become common in society, from the perspective of financial goodness, this can disrupt financial stability, both for investors and in terms of currency value stability (volatility). Although these investment ventures initially originate from real and halal activities, if they are then sold using the derivatives market sales method, they will contain elements of usury, speculation, and uncertainty which are prohibited in some sharia laws because they do not produce good in the context of investing in accordance with Islamic teachings.